Assessing facilities provided for physically challenged guests in hotels in Nairobi. - OWIDI, NICOLE AWUOR (Strathmore University, 2021)
Kenyan five-star hotels are marked as one of the best World Tourism Organization that accommodates quite a number of tourists across the globe. For a long period, the firms have provided exemplary performance in its accommodative quest for the increasing tourist who keeps on joining them. Nevertheless, research studies have indicated that People with Disabilities often face quite a number of challenges during their visit to different hotel facilities in Nairobi.
According to the Society for Accessible Hospitality (SATH), there are an estimated 1 billion persons worldwide with disabilities which represents 15% of the world’s population (APEC,2017). In Kenya, the number of persons with disabilities was reported to be 900,000 according to the 2019 census. There is a need for the development of a marketing tool for hotels that would benefit the disabled and elderly traveler that require accessible accommodation when traveling. The hotel industry has evolved for man years (Murungi, 2013), the success of the industry is tantamount to the provision of quality services to consumers.